Comparative harms assessments for cannabis, alcohol, and tobacco: Risk for psychosis, cognitive impairment, and traffic accident. (July 2022) - Johnstad, Petter Grahl
Researchers have associated cannabis use with risk for psychosis, cognitive impairment, and traffic accident. However, this review shows that the association between moderate cannabis use and psychosis is no stronger, and often considerably weaker, than the corresponding association for moderate tobacco use. The same holds for associations with cognitive impairment. For the risk of traffic accident, the review confirms that the risk from alcohol use is substantially stronger than the risk from cannabis use, while the corresponding risk from tobacco use appears to be almost as strong as that from cannabis use. It thus appears that the risk for psychosis, cognitive impairment, and traffic accident associated with cannabis use is generally comparable to that from tobacco use. The article discusses different interpretations of these comparative harms assessments and presents two points of methodological critique to argue that the risks associated with cannabis and other generally criminalized drugs are probably exaggerated. First, any measurement of harms associated with high escapist activities such as drug abuse will be affected by the general dysfunction associated with the underlying reason why a person settles for frequent escapism. From this perspective, cannabis and tobacco use disorder are probably both associated with underlying problems and life issues that are, in and of themselves, associated with psychopathology, and researchers should be careful not to conflate the selection effect from belonging to the population segment that opts for high escapist lifestyles with any (putative) harmful effect from drug use itself. Second, criminalization probably shifts the composition of the user population in the direction of more dysfunctional users. From this perspective, the association between substance use disorder and underlying problems and life issues is stronger for criminalized substances, since people who live troubled lives are less likely to be deterred by the prospect of legal problems.